Pediatric ventricular assist device thrombosis. (December 2017) - Chetan, Devin; Buchholz, Holger; Conway, Jennifer
Abstract: Pump thrombosis has best been described by Blitz as 'a riddle wrapped in a mystery inside an enigma'. This statement underscores the issues with understanding pump thrombosis including the lack of a universal definition, the optimal method for diagnosis, and the ideal strategies for prevention and treatment [1]. Most information currently available comes from adult literature, where there continues to be a lack of randomized trials or systematic reviews. The purpose of this article in not to be an exhaustive review, but rather, to synthesize major insights and developments from the recent body of literature that can help to guide diagnosis, prevention, and management of this vexing complication in the pediatric population. Highlights: Pump thrombosis is a challenging problem There is no clear universal definition in pediatrics Diagnosis and management differs by pump type Management strategies are based on adult literature Further work is need to understand the incidence of the problem, the risk factors for development and the appropriate prevention and treatment strategies